Banking Goes Digital: The Main Determinants of the Clients’ Satisfaction and Trust toward Fintech-Based Services - Rhanoui, Salma (International Journal of Economics and Financial Issues, 2022)
Financial technology, also known as Fintech, is changing banking for the better worldwide through companies with innovative business models, fresh products and services. Indeed, operators in this industry offer various financial services that were once the exclusive domain of banks; accordingly, Fintech can be an opportunity for both banks and customers. Therefore, this paper aims to identify the main features contributing to clients’ satisfaction and trust when using Fintech-based services in their banking transactions. This study presents and interprets the results of a survey on clients’ preferences and willingness to use the Fintech services offered by their banks. The scores were calculated based on analysis of variance (ANOVA) and Chi-square methods, using Python language. Even though there were minor differences in detail and other trivial variables, both methods identified the same main factors than lead to banking customers’ satisfaction with Fintech and trust in the functioning of this industry.